Pengaruh Kepemimpinan Transformasional dan Komunikasi Organisasi terhadap Kinerja Pegawai pada Biro Perencanaan dan Organisasi Badan Kepegawaian Negara: The Influence of Transformational Leadership and Organizational Communication on Employee Performance at the Planning and Organization Bureau of the State Civil Service Agency - Dita Kusuma Wardhani; Susan Rachmawati (Jurnal Mnajemen | Ekonomi | Akuntansi, 2025)
This study aims to determine the effect of transformational leadership and organizational communication on employee performance. The background of this research is the importance of the role of leaders and effective communication systems in increasing employee productivity in the work environment. The method used is quantitative through interviews, observations, and questionnaires. Data were collected through questionnaires distributed to 36 respondents. The results showed: (1) T test on Transformational Leadership has a positive and significant influence on Employee Performance with a Sig value. 0.004 < 0.05 and t count 3.119 > t table 2.034 so that partially the effect of transformational leadership on employee performance is 47.5%. (2) T test of Organizational Communication also has a positive and significant effect on Employee Performance with a Sig value. 0.003 < 0.05 and t count 3.262 > t table 2.034 so that partially the effect of organizational communication on employee performance is 48.6%. (3) The F test on the Transformational Leadership and Organizational Communication variables shows a significance value of 0.000 < 0.05 and the calculated f value of 25.040 > f table 3.28 with a simultaneous influence of 60.3%, so overall the independent variables of Transformational Leadership and Organizational Communication have a significant influence on Employee Performance